Individuality, Freedom and Socialism: The British Idealists' Critiques of the Fichtean State. (27th January 2014) - Tyler, Colin
<x xml:space="preserve">Abstract</x> Together with utilitarianism, British idealism dominated Anglo‐American philosophy from the 1870s until the end of the First World War. This article counters a persisting criticism of the British idealists: that they endorsed the allegedly oppressive and static theory of the state associated with German idealists, especially J. G. Fichte. The article introduces the British idealists' reputation as Fichtean collectivists and provides an overview of leading current interpretations of Fichte's political thought. It then analyses T. H. Green's use of Fichtean terminology against the background of Fichte's reception in Britain in the 1860s and 1870s. Edward Caird's interpretation of – and alternative to – Fichte's socialism is analysed, followed by an examination of the readings of William Wallace and Bernard Bosanquet. It is concluded that these British idealists rejected the alleged Fichtean centralism for which they have been condemned, and did so on grounds that retain force in contemporary debates between Fichte scholars.